2020
DOI: 10.1096/fj.202001035rrr
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sheep spermatogenesis through single‐cell RNA sequencing

Abstract: Spermatogenesis is an important biological process in male reproduction. The interaction between male germ cells and somatic cells during spermatogenesis, is necessary for male reproductive activities. This cellular heterogeneity has made it difficult to profile distinct cell types at different stages of development. Here, we present the first comprehensive, unbiased single-cell transcriptomic study of sheep spermatogenesis using 10× genomics single cell sequencing (scRNA-seq). We collected scRNA-seq data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
(44 reference statements)
1
33
0
Order By: Relevance
“…By knowing the changes in the transcription level of various cell types during the process of sheep spermatogenesis, Researchers found that the marker genes of early and late primary S’cytes were primarily involved in the cell cycle and related to meiosis. The other three stages were mainly related to sperm deformation such as being involved in metabolism, spermatogenesis, sperm development, and differentiation ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…By knowing the changes in the transcription level of various cell types during the process of sheep spermatogenesis, Researchers found that the marker genes of early and late primary S’cytes were primarily involved in the cell cycle and related to meiosis. The other three stages were mainly related to sperm deformation such as being involved in metabolism, spermatogenesis, sperm development, and differentiation ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified spermatogonia, spermatocytes, spermatids, Sertoli cells, Leydig cells and myoid cells through scRNA-seq. Recently, Yang et al reported characterization of sheep spermatogenesis via scRNA-seq [ 20 ]. However, spermatogonia cluster was not identified in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the laser capture micro-dissection approach has been used to precisely capture subtypes of male germ cells from paraffin tissue sections, but it leads to RNase contamination after staining [ 15 ]. Fortunately, 10 × Genomics single-cell RNA-sequencing (scRNA-seq) is an unbiased approach with high efficiency and sensitivity in cell capture, and it has been used to decipher the dynamic process of spermatogenesis in mouse, primate and sheep testis [ 16 20 ]. However, the gene expression profiling of spermatogenic cells at each sub-stage during spermatogenesis and their regulatory networks in pigs have not been uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…Although scRNA-seq technology has been successfully used to construct a map of human spermatogenesis [22][23][24], little research has been performed on the cellular characteristics and regulatory mechanisms of spermatogenesis in domestic animals such as sheep. In only one previous study, the testes of an adult (1.5-year-old) ram were found to contain five germ cell types, two testicular somatic cell types, and an unknown type of somatic cell [25]. However, undifferentiated spermatogonial cells, essential for long-term spermatogenesis, were not captured, and so the underlying mechanisms regulating spermatogonial cell self-renewal/differentiation and spermatogenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%